Feasibility of PV Integrated Microgrids in Remote North Canadian Communities. - Tim Yusishen; Amin Hajihosseinlu; Mathias Pielahn; Iman Kaffashan; Azita Fazelkhah; Dharshana Muthumuni (International Journal of Smart Grid and Sustainable Energy Technologies, 2019)
In this paper a methodology for a transition away from a fossil fuel dependency to clean energy in remote communities in northern Canada is presented. Both technical and non-technical obstacles associated with such a transition to clean energy are outlined. A proposal on how to possibly overcome these obstacles is also presented. The technical aspect of this work includes a case study on one of the communities in northern Manitoba, Canada. The case study is supported by simulations, using the software tool PSCADTM/EMTDCTM. The simulation result illustrates how the control system coordinates various parts of a microgrid and reduces annual diesel consumption.